PENGARUH SUKU BUNGA KREDIT INVESTASI PERBANKAN DAN NILAI TUKAR (KURS) DOLLAR AMERIKA (US$/RP) TERHADAP PINJAMAN LUAR NEGERI SWASTA DI INDONESIA - B01108001, Emma Rusmiayanti (Jurnal Pembangunan dan Pemerataan, 2012)
The titled of this research is "The Effect Credit Rate Of Interest Influence Banking and Exchange Rate Invesment (Rate) American Dollars/Rupiah (US$/Rp) Against Private Foreign Loans in Indonesian". The purpose of this study was to analyze the effect of investment credit rate of interest banking and exchange rate (rate) American dollar/rupiah (US$/Rp) against private foreign loans in Indonesian. This study uses quantitative methods, namely the processing of secondary data which is then carried out an analysis of the research object in accordance with the objectives of the study. The data used are secondary data in the form of monthly data published 2007.1-2011.12-year period from the publication of Bank Indonesia (Bank Indonesia's annual report, External Debt Statistic of Indonesia, SEKI) and other sources. From the research results can be seen that investment Credit rate Of Interest Banking has a negeative and significant impact on private foreign loans at 95% confidence level, while the Exchange Rate has positive effect and not significant on private foreign loans and the 95% confidence level. Key words: Private Foreign Loans, Investment Credit Rate Of Interest Banking, Exchange Rate.